Enriching students’ experiences, knowledge and communication skills via an Online Intercultural Programme (OIP) / Syazliyati Ibrahim ... [et al.] - Ibrahim, Syazliyati; Rafie, Siti Khadijah; Hasan, Asrol; Andin Salamat, Azni Syafena; A. Jadhav, Ravindra (Universiti Teknologi MARA, Kedah, 2023)
In the globalised world today, international communication has been made easily accessible to students from various parts of the world. Using the internet, students at all levels from different parts of the globe can connect and get to know one another. Based on this premise, an online intercultural programme between two higher learning institutions in Malaysia and India was conducted with the main objective to expose the students to international and intercultural communication. Students were asked to record their feedback on the programme as journal entries. The journal entries were then analysed using ATLAS.ti to explore the emerging themes which indicate what the students have gained the most from the programme. Analysis of the journal entries has shown that students who joined the programme have managed to gain new experiences, new knowledge and also communication skills. These three antecedents are significant variables in students’ learning since they open new and refreshing vistas in the students’ learning experiences. Hence, the online intercultural programme as the one in this study is a highly viable option to be conducted not only by institutions of higher learning but can also be organised by any other institutions at the lower and secondary levels, if there is internet connectivity and suitable devices.